Scientific Initiation as a strategy for the development of Scientific Literacy in basic education students: reflections from the Cientista Aprendiz - Pércia Paiva Barbosa; Diogo dos Santos; Sandra Maria Rudella Tonidandel (Universidade Cruzeiro do Sul, Ensino de Ciências e Matemática, 2022)
Scientific initiation has benefits for scientific education, but few studies focus on schools. Thus, we investigated a Program of Scientific Initiation offered by a private school in São Paulo. We aimed to identify: i) a number of students that were participated in this program (2006 to 2019); ii) the areas and themes that were researched by the participants; iii) possible gender differences. We analyzed some documents, did some statistical tests, and did an Open Data Categorization. We identified the growth of student enrollments, indicating an enlargement of their interest in scientific topics. We also identified a greater number of researches in Biological Sciences, but gender differences were not identified, just an asymmetry in the areas of interest of students. More spaces for the development of the Nature of Science in schools are necessary, as well as the constant dialogue about the insertion of women in scientific careers.